Of warnings and waiting: an examination of the path of information for two communities hit by Typhoon Haiyan - Ponce de Leon, Inez Z (Archīum Ateneo, 2019)
Typhoon Haiyan hit the Philippines in 2013, causing billions in damage, and taking thousands of lives. Media and researchers claimed that people did not have enough information about the storm, or did not understand the information given to them, and therefore did not evacuate. This research departs from the assumption of a knowledge deficit: it asks how people understood warnings and how information flowed from the government. This research focuses on Guiuan, a municipality that sustained heavy damage and loss of life, and the entry point of many typhoons in the Philippines. Guided by Stuart Hall’s Encoding-Decoding Theory, the researcher carried out focus group discussions with citizens and interviews with local government officials from one coastal and one inland village. Through systematic qualitative analysis of interviews and discussions, the researcher found that participants from different locations in the same municipality understood warning information differently, based on unique epistemological frames. While local government framed people as deficient in knowledge, the citizens actually called upon their previous experiences with storms in order to make evacuation decisions. However, they could not project worse scenarios from previous experience and needed a phenomenon to match an experience in real time before making an evacuation decision. These findings imply that disaster imagination, disaster memory, and disaster knowledge are all distinct concepts, and future research should examine how specific contexts frame risk. Early warning systems for storms must also take into account unique epistemological frames as a means to localize communication and engage communities in the decision-making process.